Research on Key Technologies of Virtual Coupling Control System for Autonomous-rail Rapid Tram - HUANG Qiang; YUAN Xiwen; HU Yunqing; LI Cheng; HUANG Ruipeng; TANG Xiang (Kongzhi Yu Xinxi Jishu)
To meet the demand for networked operation and accommodate tidal passenger flow resulting from the expanded applications, autonomous-rail rapid trams have significantly increased their transport capacity. However, this increased capacity has also brought pressure to traffic congestion. Aimed to improve the road traffic rate of autonomous-rail rapid transit (ART) and ease traffic congestion, this paper proposes a "virtual coupling" control system that uses a bidirectional information flow topology for autonomous-rail rapid tram, by drawing on concepts from the cooperative adaptive cruise control (CACC) in automobiles and train virtual coupling. A safe braking model of autonomous-rail rapid tram is initiatively used to derive the minimum space headway for operation safety between coupled formations, and the collaborative planning and MPC-based collaborative control algorithms utilizing an optimal control approach are applied to guarantee the safe, punctual, comfortable, and efficient operation of coupled formations. The simulation results demonstrate that the system proposed in this paper can enable autonomous-rail rapid tram to be virtually coupled at space headway less than 10 m within a speed range of 0 to 60 km/h, thus effectually promoting the transport capacity and operational efficiency of ART.